Neuropathic pain in patients with osteoarthritis of the hip before and after total hip arthroplasty. - Yohei Yamabe; Masahiro Hasegawa; Gai Kobayashi; Shine Tone; Yohei Naito; Akihiro Sudo (PLoS ONE, 2024)
Objectives The pain associated with osteoarthritis (OA) was thought to be nociceptive; however, neuropathic pain is also observed. We investigated the relationship between hip OA and neuropathic pain using the PainDETECT questionnaire (PDQ). Methods A total of 159 hips of 146 consecutive patients who underwent total hip arthroplasty (THA) with a diagnosis of OA were enrolled in this study. The prevalence of each pain phenotype was evaluated preoperatively and at 6 months postoperatively using the PDQ. Patient characteristics and numerical rating scale (NRS) scores were compared between a group with possible neuropathic pain (NP group) and a group with nociceptive pain (non-NP group). Results Before THA, neuropathic, unclear, and nociceptive pain was observed in 18, 36, and 105 hips, respectively. The prevalence in the NP group was 54 hips, accounting for approximately one-third of all hips, which decreased significantly to seven hips after THA. A significantly higher NRS score was observed in the NP group, both before and after THA. Conclusion Approximately one-third of the patients with hip OA had neuropathic pain. Therefore, neuropathic pain should be considered when treating patients with hip OA.